2022
DOI: 10.3390/molecules27103135
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Design Approach to Quantitative Expression for Quality Control of a Multicomponent Antidiabetic Formulation by the HILIC Method

Abstract: A rapid and reproducible hydrophilic liquid chromatography (HILIC) process was established for concomitant determination of remogliflozin etabonate (RE), vildagliptin (VD), and metformin (MF) in a formulation. A face-centered central composite experimental design was employed to optimize and predict the chromatographic condition by statistically studying the surface response model and design space with desirability close to one. A HILIC column with a simple mobile phase of acetonitrile (65% v/v) and 20 mM phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…3 Attimarad et al developed multicomponent antidiabetic formulation analysis. 4 Shah et al developed a liquid chromatographic method for the estimation of remogliflozin etabonate. 5 Itigimatha et al developed remogliflozin etabonate in pure and pharmaceutical formulations analysis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Attimarad et al developed multicomponent antidiabetic formulation analysis. 4 Shah et al developed a liquid chromatographic method for the estimation of remogliflozin etabonate. 5 Itigimatha et al developed remogliflozin etabonate in pure and pharmaceutical formulations analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Dhara et al developed a UV spectroscopic method for determination of remogliflozin etabonate in bulk and tablet dosage form . Attimarad et al developed multicomponent antidiabetic formulation analysis . Shah et al developed a liquid chromatographic method for the estimation of remogliflozin etabonate .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A thorough literature study was done and a few liquid chromatographic methods were identified for the respective drugs in triple combination. [1][2][3][4][5][6] As few works were reported on the simultaneous quantification of three combinations, an attempt was made to develop and validate an economically rapid, isocratic simultaneous ultra-performance liquid chromatographic (UPLC) method for metformin, vildagliptin and remogliflozin etabonate.…”
Section: Introductionmentioning
confidence: 99%